THEORETICAL FUNDAMENTALS OF FORMATION OF SCIENTIFIC CONCEPTS STUDENTS IN THE LESSONS OF CULTURAL DISCIPLINES (Pedagogy of Higher and Secondary Education, 2022)
In this article the reference of the main structural elements of the lessons of education subjects is given.